Major-element, trace-element and sulfur-isotope evidence for arc-like magmatism in the 4.0–2.9 Ga Acasta Gneiss Complex - Patrick Beaudry; Oliver Jagoutz; Ann M. Bauer; Hervé Rezeau; Jesse R. Reimink; Timothy L. Grove; Gareth Izon; Shuhei Ono (Contributions to Mineralogy and Petrology, 2025)
The Acasta Gneiss Complex (AGC) in northwestern Canada comprises Earth’s oldest known evolved crust, with zircon U–Pb ages up to 4.03 Ga. Several pulses of crustal generation and metamorphism are preserved in tonalitic and granitic gneisses spanning over one billion years, along with mafic and ultramafic rocks of unknown age. Major elements, trace elements and radiogenic isotope signatures have been invoked to suggest that these rocks preserve the local onset of horizontal tectonic processes. However, the behavior and influence of volatiles, which have a defining role in modern arc magmatism, remain unconstrained. Here we combine new whole-rock major- and trace-element data with multiple sulfur isotope analyses in 4.0–2.9 Ga Acasta gneisses and spatially associated mafic and ultramafic rocks to investigate the petrogenesis of the AGC. We use a recently-published major element-based melt hygrometer to estimate dissolved water contents for all published plagioclase-saturated Acasta meta-igneous rocks, and find modes at < 0.5 wt.% and 5 wt.% H 2 O, similar to modern arc magmas. Tholeiitic and calc-alkaline trends are both present, with the former being more prominent in the oldest (ca. 4.0 Ga) samples and in mafic rocks. Zircon trace element oxybarometry reveals a shift towards more oxidized magmatic conditions by 3.75 Ga. Sulfur isotopes record a limited range in δ 34 S values, suggesting a common igneous end-member at ~ + 1 ‰, and positively correlate with calculated H 2 O contents, with more positive values (up to + 5‰) appearing in the Paleoarchean (< 3.6 Ga). The Eoarchean (4.0–3.6 Ga) δ 34 S values are consistent with a precursor Hadean crust having an enriched sulfur isotope signature, possibly resulting from hydrous alteration or from isotopic fractionation during its formation. The temporal progression to more positive δ 34 S values is consistent with a shift towards more hydrous and oxidized magmatic differentiation. Most samples have near-zero Δ 33 S that fall along a mass-dependent fractionation (MDF) array, but one 3.5 Ga metasedimentary sample has a negative MIF Δ 33 S signature of -0.60 ± 0.01 ‰. Additionally, two granitic gneisses dated at 3.3 and 2.9 Ga preserve small positive MIF Δ 33 S values of + 0.08 ± 0.02 ‰, which could reflect recycling of sedimentary material via subduction by 3.3 Ga. Overall, our data indicate that the Acasta Gneiss Complex preserves several modes of crustal generation evolving over time, with an increasing importance of deep hydrous magmatism by 3.75 Ga and of sedimentary inputs by 3.3 Ga.